PELATIHAN MANAJEMEN UMKM DAN KEWIRAUSAHAAN DI PANTI ASUHAN ASIH LESTARI DADAP TANGERANG - Arifin Djakasaputra; Rico Candra (PROSIDING SERINA, 2021)
Asih Lestari Orphanage as a PKM partner requires MSME Management and Entrepreneurship training as a provision for the future for the children of the orphanage. The PKM Odd semester 2021/2022 was carried out based on an invitation letter no.13/YPA.AL/K/VII/2021 from the head of the orphanage, Mrs. Hana Ligia Bsc. This PKM target is expected to provide proper training related to the management of MSME Management and the spirit of entrepreneurship so that it can provide provisions for Asih Lestari orphanage students to understand the management of MSME management and entrepreneurship activities. This PKM activity has been carried out at the Asih Lestari Orphanage which is located at jl. Gardu no.1 Kosambi Barat, Tangerang 15213. The results of this training activity are shared by uploading the MSME Management and Entrepreneurship Module as the output of this PKM so that participants can download and read the Asih Lestari Orphanage for future learning materials. The method of implementing this training is done with tutorials and discussions as well as questions and answers which are all held via zoom. Conclusion This PKM has been carried out well and as a channel to increase knowledge insight to students at the Asih Lestari Orphanage.